PENGARUH FAKTOR KARAKTERISTIK PEKERJAAN DAN IKLIM ORGANISASI TERHADAP PRODUKTIVITAS PEKERJA (Suatu Kajian Pada Operator Bagian Produksi di Perusahaan Manufakturing Metal Stamping di Kota Tangerang - Banten) - Hermanto Hermanto (LPPM, 2010)
This research starting from suspect that worker productivity ( Y) determined by two principal variables that is performance and motivation of work of the workers. Variable - variable determining motivation of work for example work characteristic (x¹) and organization climate (x²).produktivity as comparison between outputs with input in set of certain in working every worker. This research general purpose is to obtain information based on empirical data about magnitude and direction of organizational work characteristic influence and climate to worker productivity. This research haves the character of